Marketing to millennials for dummies - Padveen, Corey (New Jersey : John Wiley & Sons, 2017)
Millennials make up the largest and most valuable market of consumers in the United States--but until you understand how to successfully market to them, you may as well kiss their colossal spending power away! Packed with powerful data, research, and case studies across a variety of industries, Marketing to Millennials For Dummies gives you a fail-proof road map for winning over this coveted crowd.--Provided by Publisher
Includes index
Keywords: Young adult consumers -- Attitudes; Generation Y -- Attitudes; Target marketing; Consumer behavior